Vector Competence of Aedes aegypti and Aedes vittatus (Diptera: Culicidae) from Senegal and Cape Verde Archipelago for West African Lineages of Chikungunya Virus - Diagne, Cheikh T. (The American Society of Tropical Medicine and Hygiene, 2014)
To assess the risk of emergence of chikungunya virus (CHIKV) in West Africa, vector competence of wild-type, urban, and non-urban Aedes aegypti and Ae. vittatus from Senegal and Cape Verde for CHIKV was investigated. Mosquitoes were fed orally with CHIKV isolates from mosquitoes (ArD30237), bats (CS13-288), and humans (HD180738). After 5, 10, and 15 days of incubation following an infectious blood meal, presence of CHIKV RNA was determined in bodies, legs/wings, and saliva using real-time reverse transcription–polymerase chain reaction. Aedes vittatus showed high susceptibility (50–100%) and early dissemination and transmission of all CHIKV strains tested. Aedes aegypti exhibited infection rates ranging from 0% to 50%. Aedes aegypti from Cape Verde and Kedougou, but not those from Dakar, showed the potential to transmit CHIKV in saliva. Analysis of biology and competence showed relatively high infective survival rates for Ae. vittatus and Ae. aegypti from Cape Verde, suggesting their efficient vector capacity in West Africa.